ICAR-CGIAR: Agricultural Cooperation - Mittal, R.K. (2017)
There has been a long association between the CGIAR institutions and the Indian National Agricultural Research and Education System (NARES) and their mutual collaborative efforts have contributed immensely in achieving a remarkable growth in food production in India.